PENGONTROLAN NUTRISI PADA HYDROPONIC VERTICAL TOWER TANAMANSTROBERI MENGGUNAKAN KONTROL LOGIKA FUZZY (Jurnal Mahasiswa TEUB, 2024)
Strawberries (Fragaria sp.) have high economic potential, but cultivation in lowlands is hampered by climate factors, such as temperature and solar radiation intensity. Hydroponic cultivation can be a solution to overcome this obstacle by providing measured nutrients according to plant needs. This study developed an automatic tool that measures nutrients based on dissolved particles (PPM) using the Sen044 TDS sensor, with Arduino Uno as a microcontroller and two peristaltic pumps for nutrient distribution. This tool is operated with a 12V 2A power supply and is designed to achieve a nutrient setpoint of 900 ppm. The control system used is Mamdani fuzzy logic, which includes fuzzification, rule base, inference, and defuzification. The fuzzification method applied is Min-max, while defuzification uses the Centroid method. The test results show that the nutrient control system has an accuracy of 94.65% in achieving the setpoint. The test also produces data on time constant, dead time, and steady state gain. For example, with a nutrient input of 700 ppm, the system exhibited a time constant of 1.63 seconds and a steady state gain of 18.51%/V with an output voltage of 3.75 volts. Keywords: Hydroponics, Fuzzy Logic, Nutrition Control System.